Correlation between some landscape metrics and insect species richness in coffee agroforests in Pangalengan Subdistrict, Bandung District, West Java, Indonesia - SUSANTI WITHANINGSIH; Parikesit; MUHAMMAD BURHANUDDIN RABBANY (Society for Indonesian Biodiversity, 2019)
Abstract. Withaningsih S, Parikesit, Rabbany MB. 2019. Correlation between some landscape metrics and insect species richness in coffee agroforests in Pangalengan Subdistrict, Bandung District, West Java, Indonesia. Biodiversitas 20: 3075-3085. The insect community provides valuable ecosystem services and can help maintain ecosystem integrity in human-altered landscapes such as coffee agroforests. The aim of this study was to assess the landscape characteristics of coffee agroforests in the Pangalengan Subdistrict and analyze how those characteristics influence the insect communities. Landscape metric approaches were examined to quantify landscape characteristics and the results analyzed using correspondence analysis to determine variation among samples, and simple linear regression testing was used to determine the influence of those landscape characteristics on the insect community. Seventeen sample locations varied in characteristics based on the proportion of the land cover classes, and landscape characteristics determined the number of insect species. The number of insect species showed strong negative correlation with landscape heterogeneity (R2=0.456) and number of patches (R2=0.514) and a weak positive response to the proportion of natural forest remaining (R2=0.150). Number of insect species showed a strong negative correlation to landscape heterogeneity, number of patches, and number of natural forest remaining simultaneously (R2=0.514).